The magician's guild - Canavan, Trudi (London : Orbit Books, 2013)
The Magician's Guild attempts to locate an untrained rogue mage, whose raw power and belligerent disposition could prove very dangerous to their order.
Adult.
Adult
Keywords: Magic -- Fiction; Magicians -- Fiction; Wizards -- Fiction; Magic -- Fiction; Magicians -- Fiction; Wizards -- Fiction; Fantastic fiction; Fantastic fiction